Right Lung Agenesis with Tracheal Stenosis due to Complete Tracheal Rings and Postpneumonectomy Like Syndrome Treated with Tissue Expander Placement - Yashwant Agrawal; Sandeep Patri; Jagadeesh K. Kalavakunta (Case Reports in Pulmonology)
Congenital lung agenesis is an extremely rare condition with an estimated prevalence of 34 in 1,000,000 live births. It is often associated with other congenital malformations of the skeletal, cardiovascular, urogenital, and gastrointestinal systems. We discuss the case of a 5-month-old who presented with increasing stridor over 1 month. Imaging revealed right lung agenesis, complete dextromalposition of heart, and compression of distal trachea. An intrathoracic saline tissue expander was placed which marked improved distal tracheal stenosis. In patients who are symptomatic it becomes imperative to perform surgeries to increase survival as was the case in this patient.